Screening Artificial Intelligence (AI) Menurut Hadrotus Syaikh KH. Hasyim Asy’ari: Telaah Kitab Adabul ‘Alim wal Muta’allim - Aisyah; Sopingi, Imam; Hidayati, Athi' (THORIQOTUNA: Jurnal Pendidikan Islam, 2025)
The development of Artificial Intelligence (AI) as a modern technology has significantly facilitated the process of acquiring, managing, and disseminating knowledge, including within the context of Islamic education. However, such advancement also brings critical ethical, spiritual, and academic challenges. This article aims to explore the use of AI through the lens of Islamic scholarly ethics, referring specifically to Adabul ‘Alim wal Muta’allim, a classical work by Hadrotus Syaikh KH. Hasyim Asy’ari. Using a qualitative approach and library research method, the study investigates key concepts such as sincerity in learning, respect for teachers, the importance of scholarly transmission (sanad), and the moral responsibility of knowledge dissemination. The findings reveal that while AI offers practical benefits, it must be critically filtered using Islamic ethical standards. Unrestricted use of AI in education may lead to intellectual decay, plagiarism, and the erosion of spiritual integrity in the learning process. Therefore, students and educators must not solely rely on AI, but instead uphold Islamic values and scholarly etiquette. This article recommends positioning AI strictly as a supporting tool—never as a primary authority in religious or academic discourse. Proper guidance, verification, and ethical awareness are essential to ensure that the integration of AI contributes positively to Islamic education. In this way, AI can be harnessed to enhance educational quality while preserving the ethical and spiritual foundations that are central to the Islamic intellectual tradition